Secondary tree crops boost butterfly diversity and abundance in oil palm alley-cropping systems - Ashraf, Mohamad; Hosaka, Tetsuro; Azhar, Badrul; Norhisham, Ahmad R.; Sanusi, Ruzana; Nakabayashi, Miyabi; Moslim, Ramle; Zulkifli, Raja; Tohiran, Kamil A. (Springer Science and Business Media B.V., 2026)
Conventional oil palm monocultures negatively impact biodiversity and ecosystem functioning, emphasizing the need for more sustainable production systems. Alley-cropping agroforestry, which integrates secondary crops within oil palm rows, may enhance habitat complexity and support greater biodiversity, yet its effectiveness in oil palm landscapes remains insufficiently understood. This study examined butterfly communities, a widely used bioindicator group across alley-cropping systems (oil palm planted with bamboo, black pepper, cacao, Tongkat Ali, and pineapple) and monoculture oil palm stands aged 7 and 15 years. We compared butterfly species richness, abundance, diversity, and community composition, and evaluated the influence of environmental variables including secondary-crop presence, undergrowth cover, light intensity, air temperature, and relative humidity. A total of 984 butterflies representing 58 species were recorded, with high sampling completeness in both alley-cropping (88%, 57 species) and monoculture systems (89%, 26 species). Alley-cropping treatments exhibited higher species richness and abundance than the 7-year monoculture, while the 15-year monoculture showed comparable levels to several alley-cropping systems. Shannon diversity was significantly higher in Tongkat Ali and some other alley-cropping treatments compared to monocultures, indicating more compositionally complex assemblages. In contrast, Simpson diversity showed limited differences among treatments, suggesting similar dominance structures across systems. Among environmental factors, only the presence of secondary crops significantly (p < 0.05) increased butterfly abundance and species richness. Alley-cropping systems also supported significantly more associated species (p < 0.05) and distinct community compositions relative to monocultures. Overall, alley-cropping enhances butterfly diversity and community heterogeneity in oil palm landscapes, highlighting its potential as a biodiversity-friendly alternative to conventional monoculture cultivation.